2014
DOI: 10.1007/s13202-014-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

An improved method to study CO2–oil relative permeability under miscible conditions

Abstract: Relative permeability curves are crucial parameters for reservoir engineer and reservoir commercial simulator to predict reservoir performance throughout the life of a reservoir, but meet difficulties in laboratory to obtain reliable data under miscible conditions due to the lack of proper testing and formulation methods. Up to now, most relative permeability curves are measured in short core segments by core flooding, which can hardly display miscible flooding features for early gas breakthrough and insuffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…For each combination of injection fluid and oil (Table 3), a graph of simulated oil recovery at 1.2 PVI was plotted against simulated pressure. MMP was deemed the pressure at the deflection point in the curve (Li et al, 2015). Fig.…”
Section: Slim Tube Simulationmentioning
confidence: 99%
“…For each combination of injection fluid and oil (Table 3), a graph of simulated oil recovery at 1.2 PVI was plotted against simulated pressure. MMP was deemed the pressure at the deflection point in the curve (Li et al, 2015). Fig.…”
Section: Slim Tube Simulationmentioning
confidence: 99%
“…The method of measuring experimentally sc-CO 2 and oil relative permeability curves under miscible flooding conditions is not available in the laboratory because remaining oil is displaced by sc-CO 2 through the extraction of light and intermedium hydrocarbons and dissolution of sc-CO 2 into oil at displacing pressure above minimum miscibility pressure (MMP). All publications discuss and emphasize the study of CO 2 –water relative permeability for a CO 2 –water system except the paper published by Li …”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 flooding relative permeability curves under miscible and near-miscible conditions were predicted using modeling technique. Several studies for experimentally measuring the relative permeability for water/CO 2 and H 2 S/CO 2 systems and evaluating the effect of interfacial tension and pore size distribution/capillary pressure, temperature, and pressure on CO 2 relative permeability have been done by researchers. Bennion and Bachu presented the characteristics of drainage and summarized the imbibition relative permeability of CO 2 /brine and H 2 S/brine systems for different rocks such as intergranular sandstone, carbonate, shale, and anhydrite rocks. Studies on water/gas and water/CO 2 systems have been focused on measuring accurately relative permeability in the laboratory and modifying the procedure of experiment and apparatus. , A set of relative permeability to natural gas/water tests of three core plugs have been completed experimentally at both room and reservoir conditions (temperature of 160 °C and injection pressure of 116 MPa) using the unsteady-state method . The program of Industrial Standard SY/T 5345–2007 (test method for two-phase relative permeability in rock) was used to process the relative permeability data, which showed that the relative permeabilities to water and gas at reservoir conditions were higher than those at room conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Relative permeability curves are essential in reservoir engineering as they are used in numerical modeling, dynamic analysis, and reservoir performance predictions (Abdelazim 2016;Akhlaghinia et al 2014;Li et al 2015;Parvazdavani et al 2017;Shi et al 2018;Tian et al 2015;Zhang et al 2014). However, relative permeability depends on internal and external applied stresses.…”
Section: Introductionmentioning
confidence: 99%